Pollen morphological diversity in the genus Acer L. (Sapindaceae) in Iran - Siahkolaee, Sedigheh Nikzat; Sheidai, Masoud; Assadi, Mostafa; Noormohammadi, Zahra (Acta Biologica Szegediensis, 2017)
Pollen grains of 19 specimens (representing 8 species, 6 subspecies, 3 sections) of the genus Acer L. distributed in Iran were investigated by scanning electron microscopy. Most of pollen grains were 3-zonocolpate, prolate. Based on exine sculpturing pattern, five types are distinguished: striate (frequent type), rugulate, reticulate, granular and smooth. Twenty-four pollen characters were examined by multivariate analysis. The result of multivariate analysis and exine sculpturing pattern indicated high diversity among different specimens even in specimens of a single species. Due to instability of pollen characters between and within studied specimens, they are not useful in delimitation of species, subspecies and sections. Only three species (A. velutinum, A. negundo, and A. mazandaranicum) were separated from other overlapping species. Pollen morphology does not confirm separation of subspecies and varieties in A. monspessulanum and A. velutinum.